Matrine inhibits the growth of natural killer/T-cell lymphoma cells by modulating CaMKIIγ-c-Myc signaling pathway - Jianyou Gu; Yu Zhang; Xiao Wang; Jingjing Xiang; Shu Deng; Dijiong Wu; Junfa Chen; Lihong Yu; Yan Zhou; Yaokun Wang; Jianping Shen (BMC, 2020)
Abstract Background C-Myc overexpression is associated with poor prognosis and aggressive progression of natural killer/T-cell lymphoma (NKTCL). Matrine, a main alkaloid of the traditional Chinese herb Sophora flavescens Ait, has been shown to inhibit cellular proliferation and induce apoptosis of various cancer cells. The present study investigated the effects and possible mechanisms of matrine inhibiting the growth of natural killer/T-cell lymphoma cells. Methods The effects of matrine on the proliferation, apoptosis and expression of apoptotic molecules, STAT3, LMP1, RUNX3, EZH2 and activation of CaMKIIγ/c-Myc pathway were examined in cultured NKTCL cell line NK92 cells. Results In cultured NK92 cells, matrine inhibited the proliferation in a dose and time dependent manner. The IC50 value of matrine was 1.71 mM for 72 h post exposure in NK92 cells. Matrine induced apoptosis with decreased Bcl-2 expression and the proteasome-dependent degradation of c-Myc protein in NK92 cells. c-Myc protein half-life in NK92 was reduced from 80.7 min to 33.4 min after matrine treatment, which meant the stability of c-Myc was decreased after matrine exposure. Furthermore, we found that matrine downregulated c-Myc phosphorylation at Ser62 together with the inhibition of CaMKIIγ, a key regulator of c-Myc protein in NKTCL. The downregulation of c-Myc transcription by matrine was mediated through LMP1 inhibition. We also observed that anti-proliferative activity of matrine was irrelevant to STAT3, RUNX3 and EZH2. Conclusions The results of the present study indicated that matrine inhibits the growth of natural killer/T-cell lymphoma cells by modulating LMP1-c-Myc and CaMKIIγ-c-Myc signaling pathway.